2018
DOI: 10.1097/aco.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the cannabinoid type 2 receptor system and its therapeutic potential

Abstract: The functional involvement of CB2 receptor in neuropathic pain and other neuroinflammatory diseases highlights the potential therapeutic role of drugs acting at the CB2 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 108 publications
2
99
0
Order By: Relevance
“…22) Accordingly, NITyr could obviously decrease the release of inflammatory cytokines that could induce the inflammatory cascade, thereby ameliorate central nervous systems disorders. 23) Meanwhile, lipid peroxidation products and the activities of antioxidant enzymes were strikingly ameliorated in the NITyr group consisted with our previous observations of N-stearoyl amino acids in ischemiareperfusion injury. 6) NITyr could reduce the level of MDA and enhance the activities of SOD and CAT but not GPx.…”
Section: Discussionsupporting
confidence: 73%
“…22) Accordingly, NITyr could obviously decrease the release of inflammatory cytokines that could induce the inflammatory cascade, thereby ameliorate central nervous systems disorders. 23) Meanwhile, lipid peroxidation products and the activities of antioxidant enzymes were strikingly ameliorated in the NITyr group consisted with our previous observations of N-stearoyl amino acids in ischemiareperfusion injury. 6) NITyr could reduce the level of MDA and enhance the activities of SOD and CAT but not GPx.…”
Section: Discussionsupporting
confidence: 73%
“…CB2 receptors are also present in glial cells (e.g., microglia), which were observed to be upregulated following inflammation or nerve injury [109][110][111][112]. Microglia are important mediators for neuropathic pain development [113][114][115].…”
Section: Modulation Of Cb2 Receptor Expression Under Neuropathic Painmentioning
confidence: 99%
“…CB2 receptors expressed in keratinocytes were increased under inflammatory or infectious conditions [118,119]. The presence of CB2 receptors in glial and inflammatory cells makes them attractive targets to reduce pain under inflammatory and neuropathic pain conditions [111,120].…”
Section: Modulation Of Cb2 Receptor Expression Under Neuropathic Painmentioning
confidence: 99%
“…In addition to an upregulation in AD, a substantial increase in CB 2 receptor expression has been found in human CNS tissue in a number of disorders associated with neuroinflammation, including MS, Down syndrome, and amyotrophic lateral sclerosis (ALS) [224,297,298]. It has been suggested that the upregulation and activation of the CB 2 receptor in neurodegenerative disease may be part of a type of negative-feedback loop in response to physiological stress, with the aim of limiting the inflammatory process (reviewed in [299]).…”
Section: The Cannabinoid System In Neuroinflammation and Neurodegenermentioning
confidence: 99%